(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article presents the results of a comparative clinical study aimed at improving surgical treatment methods for complicated hemorrhoids. The improved technique, which utilizes local anesthesia and a refined excisional approach, demonstrated reduced postoperative complications, lower pain intensity, and shorter hospitalization time compared to the standard method. The findings confirm the clinical effectiveness and safety of the proposed approach while maintaining high curative efficacy.